Problem gambling among a group of male prisoners: Lifetime prevalence and association with incarceration. Issue 1 (March 2015) - Riley, Ben; Oakes, Jane
Studies have shown an association between criminal offending and problem gambling; however, research concerning problem gambling among prisoners is limited. Although reported prevalence rates are high among the offending population, different screening tools have been used making them difficult to compare. The purpose of this study was to investigate the lifetime prevalence of both level 2 and 3 problem gambling among a group of incarcerated male offenders in South Australia and to examine the relationship between gambling and current term of imprisonment. The Early Intervention Gambling Health Test (EIGHT Screen) was completed by 105 prisoners. Fifty-five (52%) indicated a lifetime prevalence of problem gambling. One-fifth of all respondents reported their current term of imprisonment was related to gambling. This paper aims to draw attention to the prevalence of problem gambling among Australian prisoners. Implications are discussed with regards to problem gambling, health promotion and rehabilitation, and the importance of screening for gambling-related problems among this high-risk population.